Handy tips from the Intellectual Property (IP) Management Desk - UMP, PNC (Penerbit UMP, 2009)
Do a Prior Art search before filing your patent. What is Prior Art? Prior Art refers to scientific and technical information that exists before the effective date of a given patent application.